Facile reductive oxy-Nazarov cyclization of 2-methoxy-2, 4-hexadienoates. Issue 3 (18th January 2017) - Chen, Yang; Li, Wei-Dong Z.
Graphical abstract: Highlights: A facile method for synthesis of 5-hydroxyl cyclopentenone derivatives was reported. This transformation represents a new variant of the iso-Nazarov cyclization. The approach has great potential application in natural product synthesis. Abstract: Reduction of 2-methoxy-2, 4-hexadienoates with Dibal-H in toluene at −78 °C resulted in a facile formation of 5-hydroxyl cyclopentenone derivatives. This novel transformation was proposed as a variant of the oxy-Nazarov cyclization of the corresponding 2-methoxy aldehyde intermediate via the cationic Al-chelate as depicted in Fig. 2a.